Detection and characterization of HIV-1 specific T cell responses amongst exposed and unexposed HIV-1 seronegative individuals - Campion, S (2012)
The primary aim of this thesis was to examine whether HIV-1 specific T cell responses in HIV-1 exposed seronegative (HESN) subjects could be firstly detected and if so, conferred protection against productive infection from HIV-1. Cultured IFN-γ ELISpot found 38.7-60% of HESN subjects had detectable HIV-1 specific T cell responses. HIV-1 specific T cell responses could be titrated, were typically mediated by CD4+ T cells and tended to map to previously defined, promiscuous epitopes. In a statistically powered, retrospective study, no evidence was found to support a role for pre-existing HIV-1 specific T cell responses in either protection against or risk of HIV-1 infection. Exposure to HIV-1 impacted upon detection of pre-existing HIV-1 specific T cell responses, in terms of frequency (p=0.01), magnitude (p=0.02) and maintenance of response. This suggests, that exposure to HIV-1 was truly priming HIV-1 specific T cell responses. However, exposure to HIV-1 was not a prerequisite and HIV-1 specific T cell responses were detectable amongst HIV-1 unexposed seronegative (HUSN) donors. Similar to HESN, HIV-1 specific T cell responses detected amongst HUSN, could be mapped to the peptide level, titrated and were predominately mediated by CD4+ T cells. These T cells were shown to be detectable amongst memory CD4+ T cell subsets, suggesting they were not the result of in vitro priming. Whilst sample size was low, HIV-1 specific T cell responses, detected amongst HUSN donors were shown to be oligoclonal in TCRVβ usage. The detection of memory CD4+ HIV-1 specific T cell responses amongst HUSN opens a broader debate about the ontogeny of HIV-1 specific T cell responses, the inherent properties of the adaptive immune system and its preponderance toward degeneracy and cross reactivity. Greater understanding of these fundamental immunology questions should, improve our understanding of T cell ontogeny and hopefully prove beneficial in the design of a novel therapeutic vaccine for HIV-1.